1983
DOI: 10.1148/radiology.149.1.6611914
|View full text |Cite
|
Sign up to set email alerts
|

Cranial computed tomography and real-time sonography in full-term neonates and infants.

Abstract: The results of cranial ultrasonography (US) and computed tomography (CT) were compared in 52 full-term neonates and young infants. The chief indications for examination included: increasing head size, dysmorphic features, myelomeningocele, inflammatory disease, and asphyxia. Disorders detected included hydrocephalus, parenchymal abnormalities, intracranial hemorrhage, extraparenchymal fluid collections, and vascular and other developmental malformations. Hydrocephalus and subdural collections were seen in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ventricular and parenchymal haemorrhage is readily detectable using cUS soon after birth, and it is doubtful that this was missed in our study. The most common type of haemorrhage in asymptomatic term infants is posterior fossa subdural haemorrhage,14 which is difficult to detect on cUS15 16 and we did not see evidence of it. We mostly only performed cUS through the anterior fontanelle and had we used other acoustic windows for all infants we may have detected posterior fossa haemorrhage 15 17.…”
Section: Discussionmentioning
confidence: 55%
“…Ventricular and parenchymal haemorrhage is readily detectable using cUS soon after birth, and it is doubtful that this was missed in our study. The most common type of haemorrhage in asymptomatic term infants is posterior fossa subdural haemorrhage,14 which is difficult to detect on cUS15 16 and we did not see evidence of it. We mostly only performed cUS through the anterior fontanelle and had we used other acoustic windows for all infants we may have detected posterior fossa haemorrhage 15 17.…”
Section: Discussionmentioning
confidence: 55%
“…The goals of this study were: 1) to assess the diagnostic capability and applicability of ultrasonography in examining the lateral ventricles of 28 dogs with a persistent fon-studies. 5 ,8,93 [12][13][14]17 tanelle; 2) to document the incidence and degree of ventriculomegaly in this select group of dogs; and 3) to relate the degree of ventriculomegaly to the presence or absence of neural dysfunction.…”
mentioning
confidence: 99%
“…Therefore we followed prospectively cerebral blood flow velocity in both perinatally asphyxiated and healthy newborns with a gestational age of at least 34 weeks in the first week of life and compared the results of both groups. The infants were matched for birth weight and gestational age.To study our hypothesis that especially cerebral oedema plays an important role in the abnormal changes of cerebral blood flow velocity, we performed serial real-time ultrasonographic and computerized axial tomographic studies (if indicated) of the brain for detection of infarctions, parenchymal haemorrhage and of cerebral oedema [19,31,32,[42][43][44]. …”
mentioning
confidence: 99%